Investigation of the impacts of social media usage on youth mental health in Tunku Abdul Rahman University management and technology - Ting Tin Tin; Tan Bo Er; Chia Xin Chuan; Pang Hao Zhe; Chaw Jun Kit; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Sunday A. Afolalu; Umar Farooq Khattak (Scopus, 2024)
Social media's pervasive use among college students raises concerns about its impact on mental health and academic performance, with studies showing effects like increased stress, anxiety, and depression. Research on how social media affects mental health and academic outcomes in youth, hinders the development of effective interventions. Our research aims to investigate the impact of social media's entertainment and educational components on college students' sleep, anxiety, depression, and academic performance, providing valuable insights into the interplay between social media use, mental well-being, and academic success. A cross-sectional study at TAR UMT surveyed 160 students using questionnaires on social media use, mental health, and academic performance. The survey employed simple random and convenience sampling, focusing on TAR UMT's student demographics. Data analysis utilised IBM SPSS Statistics 26 and Process Macro, examining correlations and mediating effects. This study has found out that using social media for education or entertainment purpose had no discernible effects on academic performance (CGPA) with mediating of anxiety, depression, or sleep. The study also found out significant correlations between social media usage for entertainment and anxiety levels, as well as academic performance among university students. However, social media use for educational purposes showed no significant correlation with anxiety levels or academic performance.